Karakteristik Morfologi dan Genetik Tanaman Penghasil Gaharu (Aquilaria spp) Endemik Sumatera Barat - Satria, Benni; Gustian, Gustian; Swasti, Etti; Kasim, Musliar; Darnetti, Darnetti (Lembaga Penelitian Universitas Negeri Padang, 2008)
Agarwood (Aquilaria spp) is plant of tha important tropical forest trees,which produces a high economically valuable fragrant resinous wood. The objective of this study was to characterize the agarwood based on morphologist are genetic distance using RAPD markers. Characterizeof the agarwood based on morphologist and genetic distance by using RAPD markers is on alternative method to see variance morphologist,genetic and condition population plant agarwood (Aquilaria sp) endemic West Sumatra. This experiment was conducted at rain forest West Sumatraand Laboratory Agronomy Agriculture faculty Andalas University, and Laboratory Biotecnology Seameo Biotrop Bogor, during mar 2006 toDecember 2007.The result showed two group mayor cluster to agarwood i.e. Aquilaria malacensis and Aquilaria microcarpa endemic West Sumatra by using fenotipe variabilities and RAPD markers. Broad genetic variabilties were found for long and wide leaf width. Keyword : morfologist, genetic, Agarwood, and RAPD.